2009
DOI: 10.1098/rsbl.2009.0897
|View full text |Cite
|
Sign up to set email alerts
|

Young children with autism spectrum disorder use predictive eye movements in action observation

Abstract: Does a dysfunction in the mirror neuron system (MNS) underlie the social symptoms defining autism spectrum disorder (ASD)? Research suggests that the MNS matches observed actions to motor plans for similar actions, and that these motor plans include directions for predictive eye movements when observing goaldirected actions. Thus, one important question is whether children with ASD use predictive eye movements in action observation. Young children with ASD as well as typically developing children and adults we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 23 publications
(38 reference statements)
2
30
0
2
Order By: Relevance
“…Here, the children with ASD provide the critical comparison group because these children have been shown previously to display atypical patterns of visual attention to social interaction (30,31), attenuated reactivity to varying social affect (32), and lack of differential response to social attentional cues (28) but also intact response to physical attentional cues (28,29) and intact ability to predict and attend to physical events (31,33,34). In the current experimental paradigm, we tested blink inhibition as a marker of perceived stimulus salience, varying by group membership.…”
Section: Resultsmentioning
confidence: 99%
“…Here, the children with ASD provide the critical comparison group because these children have been shown previously to display atypical patterns of visual attention to social interaction (30,31), attenuated reactivity to varying social affect (32), and lack of differential response to social attentional cues (28) but also intact response to physical attentional cues (28,29) and intact ability to predict and attend to physical events (31,33,34). In the current experimental paradigm, we tested blink inhibition as a marker of perceived stimulus salience, varying by group membership.…”
Section: Resultsmentioning
confidence: 99%
“…monitor with an integrated infrared eye tracking system (Tobii 1750, Tobii Corporation, Sweden) placed against a dark background. The application of this advanced system in clinical studies has increased over the past years, see infant studies of Dadds et al, 2008, Falck-Ytter, 2009and Richmond and Nelson, 2009 as recent examples. The children sat in a comfortable chair at approximately 60 cm distance of the eye tracker to ensure efficient tracking of both eyes.…”
Section: Measurement Setup and Proceduresmentioning
confidence: 98%
“…In support of this claim, (Cannon & Woodward, 2008) demonstrated that predictive eye movements during action observation are disrupted by simultaneous performance of sequential finger movements, but not by the rehearsal of sequences of numbers. In a study of autistic 5-year olds, (Falck-Ytter, 2010) demonstrated that infants with autism were able to anticipate actions to the same degree as typical infants and adults. This finding suggests that even young children with autism are able to predict the actions of others and provides evidence against impaired action chaining in autism.…”
Section: Implicit Measures Of Action Understanding In Autismmentioning
confidence: 99%